Mode II Interlaminar Fracture Properties of Treated Silk Fibre/ Epoxy Composites at Low and High Temperature Range - Zulkifl, Rozli; Husna Azhari, Che (International Journal of Engineering and Technology, 2018)
Composite materials have a wide range of applications including as an automotive components. In certain applications it is exposed to various heat conditions and might affect its mechanical properties. It is important to be able to predict the behavior of the composites under different temperature settings in order to prevent failure. The GIIC properties of composite epoxy laminate with silk fibre at various temperatures have yet to be investigated by any researcher. This study was carried out to analyse the Mode II interlaminar fracture properties, GIIC of the silk fibre / epoxy composite materials when treated with silane coupling agents at different test temperatures. This property is important since it provides the measure of the materialâ€™s resistance to delamination crack propagation. Composite specimens were produced using compression moulding technique with sixteen layers of silk fabric. The matrix is an epoxy D.E.R 331 and Hardener Joint mine 905-3S. The weight ratio of mixing epoxy and hardener is 2:1. Six sets of sample were prepared using silk fibre which has undergone surface treatment for 24 hour using silane coupling agent surface treatment solution. Specimens were tested by Instron Universal Testing Machine using a three-point bending based on an end notched flexural (ENF) method. The tests were carried out at six different temperatures which are at 20 oC, 23 oC, 26 oC, 38 oC, 50 oC and 75 oC. The temperature of the specimens during testing was monitored using a thermal imager in order determine the exact test temperature. It was found that as the temperatures increases, the mode II fracture toughness decreases by up to 71%. The length of crack propagation shows that higher temperature leads to longer crack length. This could be due to the residual tension between the fibre and matrix as they have different thermal coefficient of expansion.Â Â Â Â Â